Pengaruh Karakteristik Psikologi terhadap Intensi Kewirausahaan di mediasi Sikap Kewirausahaan (Studi pada Mahasiswa di Lima Universitas Yogyakarta) - Gesa Sekar Risanti (EXERO : Journal of Research in Business and Economics, 2020)
This research aims to identify psychological characteristics, entrepreneurial attitudes and entrepreneurial intentions on students of five universities in Yogyakarta and explain how pychological characteristics affect entrepreneurial intentions which is mediated by entrepreneurial attitudes. Population in this research is all students of Universitas Gadjah Mada, Universitas Islam Negeri Sunan Kalijaga, Universitas Sanata Dharma, Universitas Atma Jaya Yogyakarta and, Universitas Sarjanawiyata Tamansiswa. Sampling method which is applied in this research is incidental sampling. 100 respondents participate in this research as the research subjects. However, only 98 out of 100 data can be analyzed further. The analysis technique employed in this research is path analysis operating SPSS 22.0 for windows. The result of this research indicates the effect of psychological characteristics on entrepreneurial intentions which is mediated by entrepreneurial attitudes.